MODELING VEHICLE TYRES DEPENDING ON THE DEGREE OF CHANGE IN EXTERNAL FACTORS - N. I. Otabayev (Modern American Journals, 2025)
This article presents a model for assessing the behaviour of vehicle tyres depending on variations in external factors, with a specific focus on the continuous feedback system that informs drivers and maintenance personnel about real-time tyre pressure. Accurate monitoring of current tyre pressure significantly reduces deviations from the average threshold, enhancing vehicle safety and operational efficiency. The proposed approach demonstrates how controlling pressure variations minimizes tyre wear and reduces unnecessary fuel consumption linked to improper inflation levels, ultimately contributing to economic and environmental benefits.
Keywords: Regularity, value, pressure, weight, tyre, load, transport.